Social Worker as SBIRT Instructor to Emergency Medicine Residents - Philippa Soskin; David Duong (Association of American Medical Colleges, 2014)
Abstract Introduction Interprofessional education is increasingly recognized and encouraged as an instructive approach to medical education. Social workers are a vital part of the medical team and provide a unique opportunity to strengthen interprofessional relationships while teaching residents valuable skills. This training module is designed to facilitate the interprofessional instruction and workplace learning of the Screening, Brief Intervention, and Referral to Treatment (SBIRT) methodology for emergency medicine residents by emergency department social workers. This module provides an overall curricular outline for the training of SBIRT "superusers" who will in turn train emergency medicine residents. Methods Included in this module are materials for the initial didactic instruction of both social worker superusers and emergency medicine residents. Our instructor's guide details how to implement the curriculum and includes a troubleshooting guide on the challenges and limitations we encountered, with suggestions on how to overcome these challenges and improve the training program. Results Ten social workers evaluated the SBIRT training lecture and role-play session. On a 5-point scale (with 1 = very satisfied to 5 = very dissatisfied), the session received a 1.10 for overall quality of the lecture, 1.00 for quality of the instruction, 1.20 for quality of the training materials, and 1.00 for training experience. All participants said they strongly agreed that the training was relevant to their career and expect to use the information gained from the training. Discussion Engaging social workers as superusers in the emergency department utilizes the unique skills of social workers, as well supports a team approach while building capacity for SBIRT.